Diagnosis of spontaneous cervical artery dissection may be associated with increased prevalence of posttraumatic stress disorder - Speck, Verena; Noble, Adam; Kollmar, Rainer; Schenk, Thomas (Journal of Stroke and Cerebrovascular Diseases, 2014)
Receiving information that one has a dissected cervical artery, which can cause a stroke at any time, is obviously traumatic, but details about the psychiatric and psychosocial sequelae are not known. We investigated the prevalence of and risk factors for posttraumatic stress disorder (PTSD) in patients with spontaneous cervical artery dissection (CD) and the impact of PTSD on their psychosocial functioning.Patients admitted because of CD between 2006 and 2010 were retrospectively examined using a diagnostic PTSD measure (Posttraumatic Diagnostic Scale). Patients between 2011 and 2012 were examined prospectively. To identify potential predictors for PTSD, we examined all patients' stress coping strategies (brief COPE inventory), anxiety and depression (Hospital Anxiety and Depression Scale), impairment by preventive medication, time since diagnosis and their neurologic (modified Rankin Scale) and cognitive status. To identify the psychosocial impact of PTSD, we examined quality of life (Short-Form 36).Data of 47 retrospectively contacted patients and 15 prospectively examined patients were included. Twenty-eight patients (45.2%) met the diagnostic criteria for PTSD. A significantly reduced health-related quality of life (HRQoL) was found in 27 patients (43.5%) for mental health and in 8 patients (12.9%) for physical health. Results of logistic regression analysis revealed that the use of maladaptive coping strategies was predictive of the disorder (P < .0001). Age, sex, mRS score, impairment caused by medication, and time since diagnosis were not predictive for PTSD. The presence of PTSD itself was the only significant predictor for reduced mental HRQol (P = .0004). Age, sex, mRS score, impairment caused by medication, and total Hospital Anxiety and Depression Scale score were not predictive for reduced mental HRQoL.PTSD seems to occur frequently in patients with CD and is associated with reduced mental HRQoL. Because the presence of a maladaptive coping style is correlated with PTSD, teaching patients better coping skills might be helpful.
EVALuna2:22243